Minimally invasive tissue engineering composites and cell printing. - Burg, K.J.L (IEEE Engineering in medicine and biology magazine)
Injectable composites combined with tissue-printing technology for improved bioengineered devices. The invisible engineering problem, the one often ignored, is the design of a readily implantable, precisely assembled cellular construct. Previous studies have consistently shown that composite tissue-engineered devises are readily implanted via minimally invasive means and, in the systems tested, produce minimal inflammation and fibrous encapsulation. Gels of optimal viscosity are able to maintain separation between the cellular scaffold and allow tissue growth. Studies with the cell/substrate printing system have shown that it is possible to define, in a controlled manner, spatial arrangement of cells within a gel substrate.